The impact of strategic dissent on organizational outcomes: A meta‐analytic integration - Samba, Codou; Knippenberg, Daan van; Miller, C. Chet (Strategic Management Journal, 2017)
Research summary : Strategic dissent represents divergence in ideas, preferences, and beliefs related to ideal and/or future strategic emphasis. Conventional wisdom in strategic management holds that such differences in managerial cognitions lead to higher‐quality strategic decisions, and thus to enhanced firm performance. However, 4 decades of empirical research have not provided consistent findings or clear insights into the effects of strategic dissent. Hence, we analyze the relative validity of predictions about these effects from both social psychological theories of group behavior and information processing perspectives on decision‐making. Then, we conduct a meta‐analytic path analysis (MASEM) based on current empirical evidence. Synthesizing data from 78 articles, we put to rest the notion that strategic dissent leads to positive outcomes for organizations and estimate how negative its effects actually are. Managerial summary : Top management teams (TMTs) set the tone and direction for their firms in important ways. Top managers, however, often disagree over fundamental issues related to strategy. Such strategic dissent affects how important decisions are made, and thus how the firm performs. In more specific terms and contrary to popular belief, strategic dissent creates not only dysfunctional relationships among top managers, but also disrupts the process by which these managers exchange, discuss, and integrate information and ideas in making strategic decisions. In short, firms have not yet generated value through numerous perspectives, ideas, and opinions among their top managers. We discuss interventions that could prove helpful in efforts to benefit from having diverse cognitions in a TMT.